Proteomic and functional analyses of the venom of Porthidium lansbergii lansbergii (Lansberg's hognose viper) from the Atlantic Department of Colombia - Jiménez Charris, Eliécer (2015)
The venom of the Lansberg's hognose pitviper, Porthidium lansbergii lansbergii, a species found in the northern region of Colombia, is poorly known. Aiming to increase knowledge on Porthidium species venoms, its proteomic analysis and functional evaluation of in vitro and in vivo activities relevant to its toxicity were undertaken. Out of 51 protein components resolved by a combination of RP-HPLC and SDS-PAGE, 47 were assigned to 12 known protein families. In similarity with two previously characterized venoms from species within this genus, Porthidium nasutum and Porthidium ophryomegas, that of P. lansbergii lansbergii was dominated by metalloproteinases, although in lower proportion. A common feature of the three Porthidium venoms appears to be a high content of disintegrins. Proteins not previously observed in Porthidium venoms belong to the vascular endothelium growth factor, phosphodiesterase, and phospholipase B families. P. lansbergii lansbergii venom showed relatively weak lethal activity to mice, and induced a moderate local myotoxicity, but considerable hemorrhage. Its isolated VEGF component showed potent edema-inducing activity in the mouse footpad assay. Significant thrombocytopenia, but no other major hematological changes, were observed in envenomed mice. In vitro, this venom lacked coagulant effect on human plasma, and induced a potent inhibition of platelet aggregation which was reproduced by its purified disintegrin components. Phospholipase A2 and proteolytic activities were also demonstrated. Overall, the compositional and functional data herein described for the venom of P. lansbergii lansbergii may contribute to a better understanding of envenomings by this pitviper species, for which specific clinical information is lacking.